Geração e controle de padrões de Moiré dinâmicos - Oliveira, Gabriela Nieva de (2009)
In the present work, the main idea is the dynamic sinusoidal phase gratings generation and control in a Bi12TiO20 photorefractive crystal. Firstly, we describe the technique to generate these gratings. Two aplications of this techniques are shown. The first one, it is about a kind of holographic Fourier synthesis in the profile of dynamic moiré-like patterns obtained by the superposition of multiple dynamics sinusoidal phase gratings. The second one, is the phase mismatch produced in sectioned holographic moiré-like patterns obtained by when a transparent thin glass plate is introduced in one of the hologram writing beams. This phase mismatch allow us to calculated the thickness of glass plate with great precision. In both experiments the holographic medium was used in anisotropic self-diffraction configuration illuminated by a He-Ne laser light source with λ = 0,633µm and in diffusion only recording mechanism.